2023
DOI: 10.3390/vetsci10020100
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Milk Thistle (Silybum marianum) Supplementation in Ducks Fed Mycotoxin-Contaminated Diets

Abstract: The medicinal plant milk thistle (Silybum marianum) has been widely used due to its hepatoprotective properties. The main objective of our study was to investigate the health protective effects of dietary milk thistle seed (MS), oil (MO), and seed cake (MSC) in ducks fed diets naturally contaminated with deoxynivalenol (DON; 3.43–3.72 mg/kg feed) and zearalenone (ZEN; 0.46–0.50 mg/kg feed). Female White Hungarian ducks were randomly allocated to four dietary treatments consisting of the control diet (C), the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…We found that serum levels of IL-6 and TNF-α were significantly reduced by the addition of 1,600 mg/kg silybin to the ration, which indicates that silybin can improve the anti-inflammatory ability of the organism and achieve the effect of organismal defense. This is similar to previous studies, also confirming the anti-inflammatory properties of silybin ( 14 , 38 ). Silybin has excellent antioxidant ability, maintaining the REDOX balance of the body by scavenging free radicals, activating the body’s antioxidant system and preventing the formation of lipid peroxides ( 13 , 15 , 27 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that serum levels of IL-6 and TNF-α were significantly reduced by the addition of 1,600 mg/kg silybin to the ration, which indicates that silybin can improve the anti-inflammatory ability of the organism and achieve the effect of organismal defense. This is similar to previous studies, also confirming the anti-inflammatory properties of silybin ( 14 , 38 ). Silybin has excellent antioxidant ability, maintaining the REDOX balance of the body by scavenging free radicals, activating the body’s antioxidant system and preventing the formation of lipid peroxides ( 13 , 15 , 27 ).…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have found that silybin reduces the formation of free radicals in injured cells, which could also serve as an explanation for the hepatoprotective properties of silybin ( 13 ). Furthermore, silybin has a protective effect on the liver of ducks fed diets containing mycotoxin ( 14 ). Some scholars have found that silybin activates the body’s antioxidant system by increasing sulfhydryl concentration and reducing power ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we developed an injection form of the drug based on extracts from the fruits of S. marianum. This allowed for a parenteral administration of silymarin in the animals, and also other biologically active compounds present in extract from the fruits of S. marianum, which have positive effects on the antioxidant and membrane-stabilizing functions, prevent hepatotoxic compounds from entering the liver cells, and enhance rates of hepatocyte regeneration (Bencze-Nagy et al, 2023;Shahin et al, 2023). At the same time, simultaneous administration silymarin with other therapeutic agents can increase its hepatoprotectory effect (Yu et al, 2018;Martyshuk et al, 2020;Santamarina et al, 2022;Nehmi-Filho et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the hepaprotectory action, S. marianum also exerted antioxidant, antimicrobial, immunomodulating, anti-inflammatory, anti-tumour, cardiovascular-protective, neuroprotective, skin-protective, anti-diabetes, and other medicinal properties (Denev et al, 2020;Islam et al, 2021). However, it is primarily known as a strong hepaprotector, mainly because of its biologically active compound silymarin (Bencze-Nagy et al, 2023;Guerrini & Tedesco, 2023). In different countries around the globe, silymarin is used in traditional medicine to treat patients with various liver diseases (Wadhwa et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The use of medicinal plants for multiple purposes can result in higher economic returns. In addition to medicinal use, S. marianum can also be used for oil extraction, a raw material for protein powder, animal fodder, and honey, which making S.marianum highly versatile and enhancing economic value ( Bencze-Nagy et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%